Are lifestyle pattern changes associated to poor subjective sleep quality?: a cross-sectional study by gender among the general Japanese population underwent specified medical check-ups in 2014 and 2015 - Hidaka, Tomoo (BMJ Open, 2020)
OBJECTIVES: Subjective sleep quality (SSQ) is defined by the satisfaction of one’s overall sleep experience and is composed of sleep depth and restfulness. It has not been clarified how poor SSQ is associated to changes in lifestyles. The purpose is to reveal the association of lifestyle pattern changes and poor SSQ. DESIGN: A cross-sectional study. SETTING: The data on basic attributes, SSQ and lifestyle such as presence/absence of smoking, exercise, physical activity, supper time close to bedtime, drinking habits and alcohol intake amount per day were obtained from database and questionnaire of specified medical check-ups in fiscal year 2014–2015 in Japan. The analysis was conducted in 2019. PARTICIPANTS: The subjects comprised 49 483 residents (26 087 men and 23 396 women), aged 40–74 years who had undergone an annual specified medical check-up from 2014 to 2015 in Fukushima Prefecture, Japan. OUTCOME MEASURE: Status of SSQ in 2015 was assessed using a question asking whether or not the subjects usually got enough sleep. Poor SSQ in 2015 and lifestyle pattern changes in 2014–2015 were compared between those who were in healthy status both in 2014 and 2015 (referent) and non-referent, using binary logistic regression analysis. RESULTS: Unhealthy lifestyle pattern for 2014–2015 was significantly associated to poor SSQ in 2015: ‘absent to absent’ in exercise for men (OR=1.472; 95% CI 1.316 to 1.647) and women (OR=1.428; 95% CI 1.285 to 1.587), physical activity for men (OR=1.420; 95% CI 1.270 to 1.588) and women (OR=1.471; 95% CI 1.322 to 1.638) and ‘present to present’ in supper time for men (OR=1.149; 95% CI 1.020 to 1.294) and women (OR=1.288; 95% CI 1.102 to 1.505). CONCLUSIONS: Healthcare workers may be able to contribute to the improvement of SSQ, focusing on changeable lifestyles.